Pengaruh Harga, Promosi Dan Kualitas Pelayanan Terhadap Minat Berkunjung, Studi Pada Taman Kuliner Paciran Kabupaten Lamongan - Adella Febrian Nanda Sari; Muhammad Ridwan Basalamah; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine the extent to which the influence of price, promotion and quality of service on interest in visiting, a study at Taman Kuliner Paciran, Lamongan Regency. The population in this study was visitors to Taman Kuliner Paciran. and the sample used in this study used the slovin approach so that a sample of 100 was obtained. The test was carried out using IBM SPSS version 21. It was found that there is a simultaneous effect between the variables Price, Promotion and Quality of Service on Interest in Visiting Studies at the Taman Kuliner Paciran, Lamongan Regency. Meanwhile, partially, price has a positive and significant effect on interest in visiting Taman Kuliner Paciran, Lamongan Regency. Promotion has a positive and significant effect on Interest in visiting Taman Kuliner Paciran, Lamongan Regency. Keywords: Price, Promotion and Quality of Service